2020
DOI: 10.21203/rs.3.rs-132408/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Cardiometabolic Risk Factors: the Case of Ethiopian Public Health Institute Staff Members

Abstract: Background: Non-communicable diseases (NCDs) are increasingly becoming the global cause of premature death encompassing cardiovascular diseases (CVDs), cancer, respiratory diseases and diabetes mellitus. However, early identification of cardiometabolic risk factors in the general population, especially among the high-risk groups has rarely been assessed in Ethiopia.Purpose: The study aimed to assess the magnitude and associated risk factors of cardiometabolic diseases among Ethiopian Public Health Institute (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Uncontrolled hypertension ranges from 11.4 to 69.9% among hypertensive patients on treatment in Ethiopia [22][23][24]. Tis may increase if the patient has type 2 diabetes; other studies have revealed that in Ethiopia, the prevalence of uncontrolled hypertension among adults increased alarmingly from 9.3% in 2011 to 23.5% in 2015 [25][26][27]. Only about 28.4% of patients were taking an antihypertensive drug [27].…”
Section: Introductionmentioning
confidence: 99%
“…Uncontrolled hypertension ranges from 11.4 to 69.9% among hypertensive patients on treatment in Ethiopia [22][23][24]. Tis may increase if the patient has type 2 diabetes; other studies have revealed that in Ethiopia, the prevalence of uncontrolled hypertension among adults increased alarmingly from 9.3% in 2011 to 23.5% in 2015 [25][26][27]. Only about 28.4% of patients were taking an antihypertensive drug [27].…”
Section: Introductionmentioning
confidence: 99%
“…NCDs, including cardiometabolic disorders, constitute a public health problem worldwide and represent one of the main sources of disease burden 8 . Increased magnitude of cardiometabolic risk markers, such as obesity, hyperglycemia, hypertension, and dyslipidemia become the leading causes of premature mortality 9 .The increasing prevalence rates of cardiometabolic disorders have led to a worldwide focus on behavioral risk factors involved in the progression of this diseases 10 .Modi able risk factors such as sedentary behavior have been believed to be the major risk factors for the development of cardiometabolic disease 11 .For example, the research identi es prolonged sedentary time as independent risk factors for cardiometabolic risk markers 12 , such as obesity 3 , increased waist circumferance 13 , and risk of type 2 diabetes and cardiovascular diseases 8 , and dyslipidemia in working adults 14 , as well as premature mortality 3 .…”
Section: Introductionmentioning
confidence: 99%